2016
DOI: 10.1016/j.healun.2016.01.840
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Hypertension After Heart Transplant: Does It Impact Outcome?

Abstract: Purpose: Acute kidney injury (AKI) is a frequent complication of cardiac transplantation and associated with adverse outcomes within the first postoperative year. This study describes the association between AKI and long-term adverse outcome after cardiac transplantation. Methods: The study population included 471 adult recipients that survived the first postoperative year. AKI was defined by the Kidney Disease Improving Global Outcome (KDIGO) criteria. Primary outcome variables were overall and renal survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…8,9 Data from the international literature also show that hypertension after transplantation is common, with an incidence of 70-90% in patients treated with cyclosporine and 30-50% in those treated with tacrolimus. 10,11 Both tacrolimus and cyclosporine may influence blood pressure levels and favor hyperlipidemia, as shown by Han et al 12 Regarding renal dysfunction, it has been demonstrated that immunosuppressive therapy with cyclosporine has improved graft function and survival time in transplant patients. However, cyclosporine-induced nephrotoxicity remains a medical challenge for post-heart transplant management.…”
Section: Post-transplant Pathology -Development Of New Clinical Conditions Favoring Infectionsmentioning
confidence: 97%
“…8,9 Data from the international literature also show that hypertension after transplantation is common, with an incidence of 70-90% in patients treated with cyclosporine and 30-50% in those treated with tacrolimus. 10,11 Both tacrolimus and cyclosporine may influence blood pressure levels and favor hyperlipidemia, as shown by Han et al 12 Regarding renal dysfunction, it has been demonstrated that immunosuppressive therapy with cyclosporine has improved graft function and survival time in transplant patients. However, cyclosporine-induced nephrotoxicity remains a medical challenge for post-heart transplant management.…”
Section: Post-transplant Pathology -Development Of New Clinical Conditions Favoring Infectionsmentioning
confidence: 97%